Polyphenols excreted in urine as biomarkers of total polyphenol intake. (November 2012) - Medina-Remón, Alexander; Tresserra-Rimbau, Anna; Arranz, Sara; Estruch, Ramón; Lamuela-Raventos, Rosa M
Background: Nutritional biomarkers have several advantages in acquiring data for epidemiological and clinical studies over traditional dietary assessment tools, such as food frequency questionnaires. While food frequency questionnaires constitute a subjective methodology, biomarkers can provide a less biased and more accurate measure of specific nutritional intake. A precise estimation of polyphenol consumption requires blood or urine sample biomarkers, although their association is usually highly complex.Results: This article reviews recent research on urinary polyphenols as potential biomarkers of polyphenol intake, focusing on clinical and epidemiological studies. We also report a potentially useful methodology to assess total polyphenols in urine samples, which allows a rapid, simultaneous determination of total phenols in a large number of samples.Conclusion: This methodology can be applied in studies evaluating the utility of urinary polyphenols as markers of polyphenol intake, bioavailability and accumulation in the body.